Gaya hidup warga tua di Malaysia dan keperluan kaunseling kelompok - Ismail, Zainab; Wan Ahmad, Wan Ibrahim; Mahmud, Zuria (Sekolah Pembangunan Sosial, 2007)
The older people which is also known as warga emas is a marginal group that has their own life style. There are older people who are still functional, active and productive in society. On the other hand there are some elderly who are considered to be unfunctional.In terms of counseling, this category of elderly needs to be given some kinds of support.One kind of support is group caunseling. Through this activity the unfunctional elderly can be involved in small group to share their problems and see the best way to solve the problems.This article discusses the way how group counseling through Adlerian perspectives help these elderly solve their problems and improve their quality of live.